Neural evidence for non-orofacial triggers in mild misophonia - Hansen, Heather A.; Stefancin, Patricia; Leber, Andrew B.; Saygin, Zeynep M. (Frontiers in Neuroscience, 2022)
Misophonia, an extreme aversion to certain environmental sounds, is a highly prevalent yet understudied condition plaguing roughly 20% of the general population. Although neuroimaging research on misophonia is scant, recent work showing higher resting-state functional connectivity (rs-fMRI) between auditory cortex and orofacial motor cortex in misophonia vs. controls has led researchers to speculate that misophonia is caused by orofacial mirror neurons. Since orofacial motor cortex was defined using rs-fMRI, we attempted to theoretically replicate these findings using orofacial cortex defined by task-based fMRI instead. Further, given our recent work showing that a wide variety of sounds can be triggering (i.e., not just oral/nasal sounds), we investigated whether there is any neural evidence for misophonic aversion to non-orofacial stimuli. Sampling 19 adults with varying misophonia from the community, we collected resting state data and an fMRI task involving phoneme articulation and finger-tapping. We first defined “orofacial” cortex in each participant using rs-fMRI as done previously, producing what we call resting-state regions of interest (rsROIs). Additionally, we functionally defined regions (fROIs) representing “orofacial” or “finger” cortex using phoneme or finger-tapping activation from the fMRI task, respectively. To investigate the motor specificity of connectivity differences, we subdivided the rsROIs and fROIs into separate sensorimotor areas based on their overlap with two common atlases. We then calculated rs-fMRI between each rsROI/fROI and a priori non-sensorimotor ROIs. We found increased connectivity in mild misophonia between rsROIs and both auditory cortex and insula, theoretically replicating previous results, with differences extending across multiple sensorimotor regions. However, the orofacial task-based fROIs did not show this pattern, suggesting the “orofacial” cortex described previously was not capturing true orofacial cortex; in fact, using task-based fMRI evidence, we find no selectivity to orofacial action in these previously described “orofacial” regions. Instead, we observed higher connectivity between finger fROIs and insula in mild misophonia, demonstrating neural evidence for non-orofacial triggers. These results provide support for a neural representation of misophonia beyond merely an orofacial/motor origin, leading to important implications for the conceptualization and treatment of misophonia.